2012
DOI: 10.1115/1.4006973
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hybrid Solar–Fossil Fuel Power Generation Systems and Performance Metrics

Abstract: A literature review of hybrid solar–fossil fuel power generation is given with an emphasis on system integration and evaluation. Hybrid systems are defined as those which use solar energy and fuel simultaneously, thus excluding the viable alternative of solar thermal plants which use fossil fuels as backup. The review is divided into three main sections: performance metrics, the different concentrated solar receiver technologies and their operating conditions, and the different hybridization schemes. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 76 publications
0
37
0
12
Order By: Relevance
“…Typical design solar shares range between 10% and 30% [2]. Note that this input solar share is merely for a certain design hour, and the actual value changes throughout the day/year.…”
Section: System Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical design solar shares range between 10% and 30% [2]. Note that this input solar share is merely for a certain design hour, and the actual value changes throughout the day/year.…”
Section: System Analysis Resultsmentioning
confidence: 99%
“…Within this concept of hybrid solar-fossil fuel power plants, there are three schemes: 1) solarized gas turbine, 2) solar steam integration, and 3) solar reforming [2]. A schematic of these schemes is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential solution for these problems is hybrid solarfossil fuel power generation. With the hybrid operation, intermittency concerns are eliminated as fuel can be used when solar is not available, and in particular, when solar reforming is used as the hybridization method, a viable storage option is obtained through the use of solar fuels [2]. Moreover, analysis of solar reforming hybrid cycles has shown that the hybridization can improve the solar energy system performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…System level studies have also been performed for steam and redox reformer hybrid cycles [2,3,18]. Specifically for the redox reformer hybrid cycle, the previous analysis done was for a reformer utilizing steam in the oxidation step [18].…”
Section: Introductionmentioning
confidence: 99%